Modern bribery law : comparative perspectives / edited by Jeremy Horder and Peter Alldridge. - Horder, Jeremy; Alldridge, Peter (Cambridge University Press, 2013)
The Bribery Act 2010 is the most significant reform of UK bribery law in a century. This critical analysis offers an explanation of the Act, makes comparisons with similar legislation in other jurisdictions and provides a critical commentary, from both a UK and a US perspective, on the collapse of the distinction between public and private sector bribery. Drawing on their academic and practical experience, the contributors also analyse the prospects for enforcement and the difficulties facing lawyers seeking asset recovery following the laundering of the proceeds of bribery. International perspectives are provided via comparisons with the law in Spain, Hong Kong, the USA and Italy, together with broader analysis of the application of the law in relation to EU anti-corruption initiatives, international development and the arms trade.